Academic libraries: - Ramírez Leyva, Elsa Ramírez Leyva M.; Marmolejo, Martha Ibáñez (Qualitative and Quantitative Methods in Libraries; Vol 6 No 1 (2017): March 2017 Issue, 2019)
The higher education institutions recognize that reading and writing is a problem among their students. The reading activities that Mexican universities undertake to help solve problems and provide alternatives to raise and improve reading skill have been identified by mapping .We used Social Mapping as the methodology to locate and display reading programmes in education, research and cultural promotion activities. We found that some academic libraries developed programs to promote academic and leisure reading. In this paper we present some research advances of different activities that offer useful information for university libraries to contributing to strengthen student’s academic reading skills.